Conceptual and category apparatus of legislation, what determines legal responsibility in pharmaceutical activity - O. H. Aleksieiev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The aim of the work – is to study the conceptual and categorical apparatus of the legislation of Ukraine, which determines the legal responsibility in pharmaceutical activities.